The association between prenatal micronutrient supplementation and early development of children under age two: Evidence from rural Guizhou, China. (May 2020) - He, Yang; Gao, Jingjing; Wang, Tianyi; Liu, Chengfang; Luo, Renfu
Highlights: 66.6% mothers in rural Guizhou did not supplement micronutrients during pregnancy. First study on the relation of prenatal supplements to child competence in Guizhou. Prenatal supplements are positively associate with early language development. Abstract: Background: Maternal nutrition has been shown to positively impact the pregnancy outcomes of women, as demonstrated by a decreased rate of infants born with below-average weight and size for gestational age. However, current evidences supporting the association between prenatal micronutrient supplementation and the early development of children is limited and mixed. Aims: This study investigates the association between prenatal micronutrient supplementation and the development of children under age two in rural area of Guizhou province, China. Methods: We interviewed the primary caregivers of 446 children 6–24 months old in the study area. Based on the caregivers' self-reported information about micronutrient supplementation of the child's mother during pregnancy, we divided their children into the supplemented group and the non-supplemented group. The interviews also collected sociodemographic information about the mother, the child, other family members and the households. We used the Bayley Scales of Infant Development III (BSID-III) to measure children's cognitive, language, motor, and socioemotional abilities and employed a multivariate linear regression model adjusted for confounding variables to estimate the association of interest. Results: Our data shows that 33.4% of mothers received micronutrient supplementation during pregnancy. Children in the supplemented-group had significantly higher mean scores in language (3.27; 95% CI: 0.42–6.13; p = 0.03) domain compared to children in the non-supplemented group. Conclusion: This study provides additional evidence for the association between prenatal micronutrient supplementation and improved language development of rural children in the first two years of life. The conclusion is of certain value to the local and even national policy makers.